Test and evaluation of aircraft avionics and weapon systems - McShea, Robert E. (AIAA education series., 2010)
The book reviews developments in the following fields: avionics; time, space, and position information; digital data busses; data reduction; data analysis; MIL-STD-1553; communications flight test; navigation systems; avionics civil certifications; electro-optical systems; infrared systems; radio detection; ranging; radar; electronic warfare; and weapons integration.